Hubungan Peran Perawat Sebagai Care Giver dengan Pemenuhan Kebutuhan Religi pada Pasien - Farradeswita Putri Muhammad; Ismawati Ismawati; Tezar Nusi (Lembaga Pengembangan Kinerja Dosen, 2025)
The role of nurses in fulfilling patients' spiritual needs is a crucial component of holistic healthcare, encompassing physical, psychological, social, and spiritual well-being. This study aimed to analyze the relationship between the nurse's role as a caregiver and the fulfillment of patients' religious needs in the inpatient ward of Dr. Chasan Boesorie Regional Hospital, Ternate. A descriptive-analytic method with a cross-sectional approach was used. A total of 33 respondents were selected through purposive sampling. Data were collected using questionnaires and observations and analyzed with the Fisher Exact Test at a significance level of 0.05 using SPSS version 16.0. The results showed that the caregiver role of nurses was very high (66.7%), while the fulfillment of religious needs was good (21.2%). Statistical analysis revealed a significant relationship between the two variables (p=0.012). In conclusion, there is a significant relationship between the nurse's role as a caregiver and the fulfillment of patients' spiritual needs, confirmed by a significance value of p<0.002. These findings highlight the essential role of nurses in addressing the spiritual aspects of patient care.